(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
Modern car industry high accuracy, efficiency and speed demand does. Competitive market under the circumstances every one car working issuer working release time reduce through expenses reduce and profit to increase movement This view​ in terms of cars assembly​ process on time impact doer factors study extremely important.